Novi RahmawatiÂ¹, RahmiÂ², Hartanti sinta MutiaraÂ³, Siti Nafa Awaliyahâ´, Ahmad Jaizâµ - Rahmawati, Novi; Mi, Rah; Mutiara, Hartanti Sinta; Awaliyah, Siti Nafa; Jaiz, Ahmad (Pascasarjana, Universitas Negeri Gorontalo, 2022)
AbstractÂ Â Â Â Â Reading is an important component that must be mastered by students, but at the time of field observations there were still many students' lack of reading comprehension due to the limited learning media available at school. The purpose of this study was to produce syllable wheel media for students' reading comprehension skills in grade II elementary school. This study uses the ADDIE development model. The subjects involved in this research were media experts, material experts, linguists and 12 grade II students at SDN 22 Indralaya. In research data collection was carried out by observation, interview and questionnaire methods. In the research instrument there are observation sheets, interviews, media expert evaluation validation, language and material, student response sheets and test sheets with pretest and pottest. The results of the study show that the results of the analysis of media, material and language experts are feasible. The students' responses were very good, easy to understand for them using the syllable wheel as a learning medium.